Crops Change the Morphology, Abundance, and Mass of Microplastics in Mollisols of Northeast China - Wang, Jiuqi; Yan, Pengke; Wang, Wan; Hao, Xinhua; Xu, Bing; Aurangzeib, Muhammad; Zhang, Shaoliang (Frontiers in Microbiology, 2022)
Microplastics (MPs) degradation by both physicochemical and biological processes in the natural environment, can be determined by the enzymes inside the soil, which was severely influenced by crop growth and straw amendment (SA). However, it is still unclear how crop growth and SA influence MPs degradation in soils. In this study, both catalase and sucrase were measured, the stereomicroscope combined with microscopic infrared spectroscopy and scanning electron microscope (SEM) was used to detect the morphology and quantity of low-density polyethylene microplastic (LDPE-MP) and low-density polypropylene microplastic (LDPP-MP), after crops' growth (maize and soybean, with- and without SA, 1% and 2% MP) in an outdoor pot experiment, in the Mollisols. The results showed that the growth of the crops changed the morphology, functional groups (e.g., methylene, carbonyl), total mass, and abundance ratio of different size MPs. These were possibly caused by enzymes, which were significantly influenced by crop types, abundance, and types of MP in the soils. Maize growth decreased the mass of LDPE-MP and LDPP-MP by 28.7% and 32.7% respectively, and 2% (w/w) of LDPP-MP addition in soil decreased mass of 9% which was higher than that in 1% (w/w) LDPP-MP addition in soil. Soybean growth with SA decreased the mass of LDPE-MP and LDPP-MP by 36.6% and 20.7% respectively than the control treatment (CK). Compared with CK, both crop growth and SA changed the abundance of different size MPs and decreased the mean size of MPs. The LDPE-MP could be more easily degraded by enzymes in the soils compared to LDPP-MP when MP size was smaller with surface roughness. Generally, both maize and soybean growth can accelerate MP change in soils, and MP change process was mainly influenced by SA, MP types and the dose effect of MP.